Balthasar Hubmaier and the clarity of scripture a critical reformation issue - Chatfield, Greame R. (Cambridge : James Clarke & Co, 2013)
Of Writings from late 1525 to July 1526, Published 1526-277. Making a Patchwork of Scripture; Introduction; Old and New Teachers on Believers' Baptism; A Brief Apologia; A Simple Instruction; A Christian Catechism; The Ground and Reason; On Fraternal Admonition; A Form for Water Baptism; A Form for Christ's Supper; On the Christian Ban; Freedom of the Will I; Freedom of the Will II; Summary of writings at Nikolsburg from July 1526 to July 1527; 8. Judge Me According to the Word of God; Apologia; Summary of writings from January to March 1528.
During the sixteenth century, many Reformers echoed Erasmus's claim that the Scriptures were clear, could be understood by even the lowliest servant, and should be translated into the vernacular and placed in the hands of all people. People did not require the magisterium of the Roman Catholic Church to correctly interpret the meaning of the Scriptures. However, within a few short years, the leaders of the Magisterial Reformers, Martin Luther and Huldrych Zwingli, had created their own Protestant versions of the magisterium. This work traces how the doctrine of the clarity of Scripture found e.
9. Hubmaier's Hermeneutic: "Truth is Unkillable"Scripture; Clarity of Scripture; The Commands of God and Forbearance; Christology; Government; Anthropology; Conscience; Languages and Interpretive Method; Assessment; Bibliography; Back Cover.
Includes bibliographical references.
Print version record.
Master record variable field(s) change: 072
Keywords: Hubmaier, Balthasar, -- -1528.; Bible -- Hermeneutics; Bible -- Criticism, interpretation, etc. -- History -- 16th century; Hubmaier, Balthasar, -- -1528.; Bible; Anabaptists -- Doctrines; RELIGION -- Christianity -- Protestant; Anabaptists -- Doctrines; Hermeneutics; RELIGION / Christian Church / History; 1500-1599; Electronic books; Criticism, interpretation, etc; History